Civil status and educational attainment of tricycle drivers in UPV-Miagao as predictors of perception towards sexual harrassment and gender roles. - De Leon, Maria Angela A.
This study is aimed to discover if several factors such as Civil status and Educational attainment can predict different perceptions when it comes to sexual harassment and gender roles of tricycle drivers in Miagao UPV campus. Thirty drivers whose routes enter UPV participated in the survey given. Two questionnaires were given to the participants, one being the gender roles belief scale and the sexual harassment scale. Results of the study showed that the factors mentioned above did not affect the perception towards the sensitive topic of sexual harassment and gender roles. In such case that the rural setting of the environment and age of these participants might have affected their perception towards the topic.